The Cosmos in a Cabinet: Performance, Politics, and Mechanical Philosophy in Henry Bridges' 'Microcosm'. Issue 1 (March 2019) - Sampson, Paul E.
Highlights: In 1733 an automaton theater dubbed the "Microcosm" debuted in London and purported to show the entire Newtonian universe. Throughout its 40-year career, its proprietors claimed that it promoted virtue, patriotism and religious orthodoxy. However, evidence shows that middling audiences were eager to reinterpret their lowly position within this elite cosmology. Abstract: How did ordinary people – artisans, laborers, servants, and children – come to know the Newtonian universe? And what effects did this knowledge have on how they contextualized their place in society? When it appeared in 1733, Henry Bridges' "Modern Microcosm" promised to give paying customers a view of the entire universe ingeniously recreated in a ten-foot-tall automaton theater. A hit with audiences, this clockwork wonder was displayed in Britain and the American colonies until disappearing mysteriously in the 1770s. This paper attempts to recover non-elite understandings of public science by examining the career of an astronomical wonder in the rowdy marketplace of ideas that was the London show scene.